PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN PENDEKATAN CTL KELAS V SEKOLAH DASAR SWASTA PERTIWI - Setiawati, Restu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract A common problem in this research is whether the CTL approach can improve the narrative writing skills of VB class SDS Pertiwi Pontianak Tenggara? The general objective of this research is to improve the narrative writing skills by using CTL VB class SDS Pertiwi Pontianak Tenggara. This research used a descriptive method with class action research form, and the nature of research is collaborative. The research took place in SDS Pertiwi of Pontianak Tenggara with research subject is student of VB class which amounted to 26 people. Data collecting technique used is direct observation technique with data collection tool that is observation sheet and measurement with data collection tool test. The collected data is analyzed by calculation of averages and percentages. This research is done as much as II cycle with 2 times meeting at every cycle. The results obtained are the ability of teachers in designing learning in the first cycle with an average score of 3.17, second cycle increased to an average score of 3.93. The result of the teacher's ability to carry out the learning on the first cycle with an average score of 3.29, on the second cycle with an average score of 3.98. Student learning outcomes on learning narrative writing skills on the first cycle average is 75.78 and the average cycle II is 83.07. From the analysis of data that were obtained, this shows that the use of CTL approach can improve narrative writing skills. Keywords: Improvement, Writing Skill, Essay of CTL Approach